The Backbone: Construction of a Regional Electricity Grid in the Arabian Peninsula. Issue 2 (2nd September 2018) - Günel, Gökçe
ABSTRACT: This article studies the production of a power grid across six Gulf Cooperation Council (GCC) countries, known as 'the backbone, ' which has been conceptualized as an answer to power outages. First it analyzes how experts working with and around the GCC Interconnection Authority (GCCIA) advance claims to a regional territorial imagination. Second, it shows that the construction of the grid not only indicates a shift in the material arrangement of wires and substations, but also necessitates new understandings of transparency and a new formula for the electricity price, facilitating the cutting of government subsidies along with additional price increases. Third, it interrogates how electricity is consumed in the region. Policy-makers expected that electricity price increases would lead to lower rates of consumption. Yet after price hikes were instituted, analysts reported how they had no impact. Users behaved in ways that the grid's engineers did not anticipate. Overall the article shows how various actors conduct 'boundary work, ' that is, how they set limits between the political, the financial and the technical while producing the backbone. The article explores how this boundary work helps stabilize a particular sociotechnical imaginary of energy security in the GCC, masking anxieties associated with a future beyond oil.